The bumblebee - Sheehan, Angela; Pledger, Maurice (New York : Warwick Press, 1976)
Describes the life cycle and natural environment of the bumblebee.
Keywords: Bumblebees -- Juvenile literature; Bumblebees; Bees; Abelhas